The Governing Bodies of the KGB of the Lithuanian Soviet Socialist Republic in 1954–1991 - Okuličiūtė, Lina (Genocidas ir rezistencija, 2007)
This article analyses the governing bodies of the KGB of the Lithuanian SSR from 1954 to 1991, revealing the process and development of the leadership. The main functions of the chairmen were emphasized by how suppressed the anti-Soviet movement was, by fighting against the Catholic Church and émigré organizations. The activities of the KGB chairmen of the LSSR reflect the policy of the control mechanism.The KGB consisted of a chairman and three deputy chiefs. The first deputy chief was always Russian, and the scope of its authority included controlling the operative work. The second deputy was a local KGB recruit, and he controlled political surveillance. The third deputy was responsible for the supervision of the KGB personnel, and alongside, exercised the functions of the head of the Personnel Department. The KGB chairman together with his deputies, the heads of major directorates and departments and the heads of the KGB departments of the biggest towns formed the Board of the Lithuanian KGB, which dealt with major issues of the KGB organizational work like reports by the heads of departments and directorates, the major draft instructions and decrees, and so on.
Keywords: KGB; KGB governing bodies; communist party; repressions